Crossover from collective to incoherent spin excitations in superconducting cuprates probed by detuned resonant inelastic X-ray scattering - Minola, Matteo; Haverkort, Maurits W. (Physical review letters, 2017)
Spin excitations in the overdoped high temperature superconductors Tl2Ba2CuO6+δ and (Bi,Pb)2(Sr,La)2CuO6+δ were investigated by resonant inelastic x-ray scattering (RIXS) as functions of doping and detuning of the incoming photon energy above the Cu−L3 absorption peak. The RIXS spectra at optimal doping are dominated by a paramagnon feature with peak energy independent of photon energy, similar to prior results on underdoped cuprates. Beyond optimal doping, the RIXS data indicate a sharp crossover to a regime with a strong contribution from incoherent particle-hole excitations whose maximum shows a fluorescencelike shift upon detuning. The spectra of both compound families are closely similar, and their salient features are reproduced by exact-diagonalization calculations of the single-band Hubbard model on a finite cluster. The results are discussed in the light of recent transport experiments indicating a quantum phase transition near optimal doping.